Dynamic Mathematical Models of Mineral Water Production for Community Consumption - Suksomboon, Rattapol; Poosumrong, Laongdaw (Burapha Science Journal, 2024)
Background and Objectives : The objective of this study was to develop the dynamic modeling of Recirculation Ring Plug-Flow Reactor (RRPFR) and Recirculation Ring Completely-Mixed Stirred Tank Reactor (RRCSTR) of a Recirculation Ring Drown Flow Filter Reactor of Groundwater (RRFRG). Methodology :The flow direction is perpendicular to the Recirculation Ring Drown Flow-cylindrical reactor. The inflow into the iron reactor diameter 0.15 m., height 4 m., connected to the second resin reactor, diameter 0.15 m., height 1.2 meters of 12 reactors had a diameter to length ratio (D:L) (<1:4) Main Results :It was found that the ratio (R) was 3 with the background concentration iron (Fe*) and the background concentration hardness (CaCO3*) were 0.071 and 0.032 mg/L. The hydraulic retention time (HRT) at 0.09 day was the highest efficiency to remove Fe and CaCO3 were 99.867% % and 99.996 % in groundwater. Conclusions : The development of the mathematical model, it was found that second-order reaction occurred in Recirculation Ring Completely-Mixed Stirred Tank Reactor (RRCSTR) with a coefficient of constant k2nd were 3396.80 1/day and 11091 1/day.